1998
DOI: 10.1002/(sici)1521-4141(199808)28:08<2571::aid-immu2571>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Formation of TCR dimers/trimers as a crucial step for T cell activation

Abstract: T cell activation involves specific interactions between the TCR and peptides presented by the MHC. This engagement leads to phosphorylation and subsequent internalization of the TCR complex. By analyzing the kinetics of the internalization of TCR, we found that the rate of TCR down-regulation was proportional to the square of the TCR density. Mathematical modeling of TCR interactions indicates that such a relation is only possible if TCR dimerize before internalization. By mathematical analysis, our data woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 43 publications
0
28
0
1
Order By: Relevance
“…Recently activated T cells show reduced TCR surface expression levels (59,60). We therefore reasoned that TCR expression levels might differ in CD62L…”
Section: Cells Have Reduced Surface Tcr Expression Levelsmentioning
confidence: 99%
“…Recently activated T cells show reduced TCR surface expression levels (59,60). We therefore reasoned that TCR expression levels might differ in CD62L…”
Section: Cells Have Reduced Surface Tcr Expression Levelsmentioning
confidence: 99%
“…Studies by Zhang et al (18) have shown that TCR-mediated signaling is enhanced upon oligomerization (11). This aggregation of TCR resulting in increased signaling efficiency may be influenced by the recruitment of these receptors into lipid rafts upon engagement with peptide/MHC molecules on APCs (12).…”
mentioning
confidence: 99%
“…Previous mathematical analysis of T cell responses have been successful in modeling specific features such as fast ligand dissociation kinetics (6), peptide antagonism (7,8), rate of receptor internalization (9), or the effect of co-stimulation on proliferation (10). Current models favor a discrimination between the potency of TCR ligands based on the life-time of the interaction, i.e.…”
Section: Most T Cells Present ␣␤ T Cell Receptors (Tcr)mentioning
confidence: 99%
“…Current models favor a discrimination between the potency of TCR ligands based on the life-time of the interaction, i.e. the off-rate (6,7,9). In Support, recent studies suggest that TCR signaling correlates to ligand dissociation rate (11)(12)(13).…”
Section: Most T Cells Present ␣␤ T Cell Receptors (Tcr)mentioning
confidence: 99%